Fast Generalized Spatial Multilevel blockNNGP Modeling - (:unkn) unknown (Elsevier BV, 2024)
Typical geostatistical models only consider the case where we observe one response at each location. However, the situation with multiple replicates at spatial locations is seldom discussed. Moreover, the generalized spatial Gaussian process models encou...
Keywords: Modelos espaciales; Estadística bayesiana